TÉCNICA PARA REDUÇÃO FACILITADA DE FRATURA SUBCONDILAR - RELATO DE CASO - Goldschmidt Follmann, Laura (2023)
Condyle fractures are unique from a functional point of view, and it’s incidence is variable. Among the possibilities of treatment, the closed treatment/non-surgical or open reduction/surgical are well established, but the choice for it’s indication remains controversial, and some variables must be taken in account.  It’s known that the open reduction, when indicated, provides early functional reestablishment and less functional long-term complications. The objective of this case report is to present a technique that facilitates the anatomic reduction of subcondylar fractures, especially those when bone fragments are overlapped, through the retromandibular access, using just a number 12 bicortical screw, a number 14 Abocath needle and a number 2 steel wire. Pacient N.B.V, 62 years old, woman, facial politrauma victim caused by car accident. Among the multiple facial fractures, the pacient had a subcondylar fracture on the left side, with loss of height of mandible ramus, which underwent surgical treatment with open reduction of the fracture using the technique described. It can be concluded that the technique, in the case, was considered appropriate, facilitating the anatomical reduction of the fractured segments and, as a result, satisfactory function and low postoperative morbidity were obtained.